Investigating web-based recruitment sources: Employee testimonials vs word-of-mouse - VAN HOYE, Greet (Institutional Knowledge at Singapore Management University, 2007)
Although the internet has dramatically changed recruitment practices, many web-based recruitment sources have not yet been investigated. The present study examines the effects of web-based employee testimonials and web-based word-of-mouth (i.e., 'word-of-mouse') on organizational attraction. The source credibility framework is used to compare these company-dependent and company-independent recruitment sources. In a sample of potential applicants for a head nurse position, word-of-mouse was associated with higher organizational attractiveness than web-based employee testimonials. However, potential applicants were more attracted when testimonials provided information about individual employees than about the organization. Conversely, word-of-mouse was associated with higher organizational attractiveness and more organizational pursuit behavior when it focused on the organization instead of on employees. Most of these effects were mediated by credibility perceptions.